2014
DOI: 10.1126/science.1236828
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of early Homo : An integrated biological perspective

Abstract: Integration of evidence over the past decade has revised understandings about the major adaptations underlying the origin and early evolution of the genus Homo. Many features associated with Homo sapiens, including our large linear bodies, elongated hind limbs, large energy-expensive brains, reduced sexual dimorphism, increased carnivory, and unique life history traits, were once thought to have evolved near the origin of the genus in response to heightened aridity and open habitats in Africa. However, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
351
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(378 citation statements)
references
References 134 publications
17
351
0
10
Order By: Relevance
“…Although any event that altered the evolutionary cost/benefit analysis of either brain expansion generally (4,8) or high-fidelity social learning specifically (2, 16) could theoretically have initiated runaway biocultural coevolution in our lineage, there is no reason to assume this feedback would be indefinitely self-sustaining once initiated, nor that that it would necessarily produce constant increase as opposed to more complex dynamics. In fact, both comparative biological evidence (4) and cultural evolutionary models (19) indicate the potential for just such interactions and dynamics and this is entirely consistent with the emerging paleoanthropological picture of multilineal, intermittent, asynchronous change over human evolution (20,21). This indication suggests a more contingent evolutionary history, likely involving multiple inflection points in response to perturbations both intrinsic (19) and extrinsic (20) to hominin behavior systems.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Although any event that altered the evolutionary cost/benefit analysis of either brain expansion generally (4,8) or high-fidelity social learning specifically (2, 16) could theoretically have initiated runaway biocultural coevolution in our lineage, there is no reason to assume this feedback would be indefinitely self-sustaining once initiated, nor that that it would necessarily produce constant increase as opposed to more complex dynamics. In fact, both comparative biological evidence (4) and cultural evolutionary models (19) indicate the potential for just such interactions and dynamics and this is entirely consistent with the emerging paleoanthropological picture of multilineal, intermittent, asynchronous change over human evolution (20,21). This indication suggests a more contingent evolutionary history, likely involving multiple inflection points in response to perturbations both intrinsic (19) and extrinsic (20) to hominin behavior systems.…”
supporting
confidence: 51%
“…In fact, both comparative biological evidence (4) and cultural evolutionary models (19) indicate the potential for just such interactions and dynamics and this is entirely consistent with the emerging paleoanthropological picture of multilineal, intermittent, asynchronous change over human evolution (20,21). This indication suggests a more contingent evolutionary history, likely involving multiple inflection points in response to perturbations both intrinsic (19) and extrinsic (20) to hominin behavior systems. If this is the case, understanding coevolutionary feedback dynamics (4,8) and CE processes (2,19) will be necessary but not sufficient to explain the actual path of human evolution, which will additionally require the application of these general principles to explain particular historical contingencies (17).…”
supporting
confidence: 51%
“…Using the doubly labeled water (DLW) technique to quantify total daily energy expenditure (TEE; kcal/day), they have shown that humans have systematically and significantly greater energy budgets than chimpanzees, gorillas, or orangs. It appears likely that the elevation in human total energy demands initially emerged with the evolution of the Homo, in association with a foraging regime that was exploiting more animal material and required movement over larger areas than was typical of earlier hominin species [29,32,33].…”
Section: Tool Use and Foraging Strategiesmentioning
confidence: 99%
“…afarensis and 18.7 for H. erectus s.l., variability in the two groups is also not significantly different (Fligner-Killeen test, p . 0.3); if variability is a valid surrogate for adaptability [21], there appears to be no adaptive advantage within the pooled H. erectus group or within African H. erectus. In contrast, the pooled H. erectus sample is significantly larger than the pooled early African Homo (plus H. habilis) sample ( p , 0.01).…”
Section: Synopsis Of Body Size Evolution In the Human Careermentioning
confidence: 99%
“…We are especially interested in examining the body size of early Homo and Homo erectus, because there is a widely held belief that the emergence of the genus Homo and the successful dispersion of H. erectus out of Africa are linked causally to increased body size from some smaller, ancestral australopith [16][17][18][19][20][21][22][23][24]. Larger body size in Homo is believed to have 'important energetic, locomotor and survival consequences' [18, p. S272] and could involve changes in home range, foraging strategies, energy budgets and encephalization [20].…”
Section: Synopsis Of Body Size Evolution In the Human Careermentioning
confidence: 99%